Beck Hopelessness Scale (BHS): Adaptation and psychometric characteristics - Aliaga Tovar, Jaime (2006)
In this paper we presented the adaptation and psychometric study of the Beck Hopelesness Scale (BHS). The sample consisted of 782 subjects (372 males and 445 females) The median age was 19 years. The sample this conformated by suicide attempters (n=26); recurrent-episode major depression and bipolar disorder patients (n=23); hipertensives, asmathics and tuberculosius patients (n=68); paranoid schizophrenics and affective disorders patients (n=22); PBC addicts (n= 25); 6th.grade primary students (n= 51); housewives, secondary and universitary students, teachers (n= 567; general population). The Alpha Crombach´s was 0.80 (N= 782) and the Pearson correlation between the test-retest scores for sample (n=100) who were tested at intake and two weeks later was 0.60. The correlation between the BDI Hopelesness/Pessimism item and the BHS was 0.46; the correlation between the BDI subtracting Hopelesness/Pessimism item and the BHS was 0.40. The Factor Analysis of the items whit components principal and varimax rotation techniques found six factors explained the 49.32 of variance. The BHS score was not significantly related to sex but was positively related to age (p<0.01). Finally, the major depression and bipolar disorders patients agrupated in moderate and severe range hopeleness; the general population and the asmathics, hypertensives, tuberculous and PBC addicts patients agrupated in normal and mild range hopelessness. Concluding at the end that the BHS evaluated psychological significative construct and may to be used for screening.